Cultural hybridisation in Lisbon's musical projects : a European perspective on multicultural and intercultural policies - Molard, Arthur Félix (2024)
This dissertation explores multicultural and intercultural policies in Lisbon, examining both local and European perspectives. Specifically, it addresses the guidelines that counter the notion that cultural diversity negatively impacts society, and it delves into the influence of these policies on the ongoing process of cultural hybridisation within collective musical projects based in Lisbon. The existing dialogue between the sectors of society (focusing on the government, policy makers and the civil society) enables me to analyse these impacts by contrasting cultural hybridity and hybridisation of music creation in two collective musical projects in the intercultural context of Lisbon: the Orquestra TODOS and Krusty Fondant. This discussion, mainly articulated by the intergovernmental organisation for Human Rights Council of Europe, puts in perspective the emergence of multicultural and intercultural policies in European cities and their pondering around cultural diversity, integration, inclusivity, cultural hybridisation and citizenship in the European project. I analyse the changes of the political concerns (discourses and actions) on cultural diversity, inclusivity and openness (figurative and physical) of Portugal, analysing the reports, strategies, tools and research conducted by the Council of Europe and by the Lisbon Municipality (Câmara Municipal de Lisboa) and try to grasp their effects in collective musical projects in Lisbon. I conduct field work in the analysis of my case studies using an ethnographic methodology focused on field observation and ‘responsive’ interviewing of members of the aforementioned musical projects. I therefore aim to enlighten the current integration of collective hybrid musical projects in Lisbon’s cultural landscape.